2001
DOI: 10.1007/s002340000500
|View full text |Cite
|
Sign up to set email alerts
|

MRI techniques and cognitive impairment in the early phase of relapsing-remitting multiple sclerosis

Abstract: Correlation studies between various conventional and non-conventional MRI parameters and cognitive impairment in the early stages of multiple sclerosis (MS) are lacking, although it is known that a number of patients with early MS have mild cognitive impairment. Our aim was to explore whether this cognitive impairment is dependent on the extent and severity of the burden of disease, diffuse microscopic brain damage or both. We studied 63 patients with clinically definite relapsing-remitting (RR) MS, duration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
101
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(113 citation statements)
references
References 0 publications
9
101
1
2
Order By: Relevance
“…For example, in five cross‐sectional18, 23, 24, 25, 26 and two longitudinal studies,2, 38 which included between 43 and 81 patients in very early stages of MS, no significant associations between MRI lesion burden and cognitive measures were reported. Four of these studies also examined the relationships between global or regional brain atrophy and cognitive measures but found no associations 2, 24, 25, 26.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in five cross‐sectional18, 23, 24, 25, 26 and two longitudinal studies,2, 38 which included between 43 and 81 patients in very early stages of MS, no significant associations between MRI lesion burden and cognitive measures were reported. Four of these studies also examined the relationships between global or regional brain atrophy and cognitive measures but found no associations 2, 24, 25, 26.…”
Section: Discussionmentioning
confidence: 99%
“…However, a correlation between conventional MRI findings and clinical impairment is weak. The most important factor seems to be the subtle abnormalities within normal appearing white matter (NAWM) which cannot be delineated by conventional MRI and contribute to the development of disability in MS [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Given that cerebral atrophy is increasingly associated with worsening MS, volumetric analysis has also been the focus of much recent research on cognition. Studies looking at total brain parenchymal volume have indicated that global atrophy is strongly correlated with development of cognitive dysfunction in MS [29][30]. When the association between volume and size of individual structures (e.g., ventricle width, bicaudate ratio) and cognitive dysfunction was examined, central atrophy as measured by the third ventricle width more strongly predicted cognitive dysfunction than either global atrophy or lesion load [31].…”
Section: Imaging Characteristicsmentioning
confidence: 99%
“…Pan et al found significant correlations between high periventricular N-acetyl aspartate levels and impaired performance on cognitive testing [34]. In sum, mounting evidence indicates that damage to white and gray matter structures within the CNS is significantly correlated with cognitive dysfunction in MS [29][30][31][32][33][34][35]. Continued study and improved imaging techniques may better elucidate the pathology of cognitive dysfunction in MS and the compensatory mechanisms that MS patients with cognitive dysfunction use.…”
Section: Imaging Characteristicsmentioning
confidence: 99%